Rules of Engagement: Sport Sponsorship, Anti-Ambush Marketing Legislation, and Alcohol Images during the 2011 Rugby World Cup. Issue 3 (3rd July 2018) - Gee, Sarah; Thompson, Ashleigh-Jane; Batty, Rachel J.
ABSTRACT: In 2011, New Zealand/Aotearoa hosted the Rugby World Cup (RWC). Heineken's sponsorship rights as RWC Worldwide Partner and the official beer offered the global conglomerate sole promotional and advertising privileges for all official events, activities, and facilities associated with the event. Yet, local New Zealand beer brand Steinlager also had a vested interest in the tournament considering their 25-year sponsorship of New Zealand's national rugby team, the All Blacks. This study articulates Steinlager's 'We Believe' promotional campaign during the 2011 RWC with various socio-historical and political-economic contexts to understand its contested production, meaning, and regulation. Using a critical analysis of the Steinlager 'We Believe' television advertisement, wider promotional campaign, and an interview with a key media producer, the findings are presented and discussed within the context of New Zealand's Major Events Management Act, ambush marketing, and the emergence of social media to leverage Steinlager's brand presence during the tournament.